A BRIEF REVIEW OF SIYASAH SYAR'IYYAH ON THE AUTHORITY TO SUPERVISE THE OPERATION OF ONLINE BAJAJ TRANSPORT IN MAKASSAR CITY - Ahmad Zuhry Amir; Nurul Aulia Fitra; Zakirah Zakirah; Andi Muh. Taqiyuddin BN; Nur Alimahmudrikah R (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to discuss a brief review of Siyasah Syar'iyyah on the authority of the Makassar City Government in supervising the operations of online bajaj transportation. This study is qualitative in nature. The research design is field research with a juridical-empirical and normative-sharia approach. The informants interviewed in this study were the Makassar City Transportation Agency (Acting Head of the Public Transportation Section), the Makassar Police Traffic Unit, the Maxride application provider (Business Development and Customer Support), online bajaj drivers, and users. The results of this study show that: There is no supervision of online bajaj by the government, aspects of operational supervision, online bajaj do not receive equal supervision because there are no specific regulations, many drivers do not understand the routes, there is no training, and vehicles operate without certainty of permits. The Makassar City Government has not exercised maximum supervision because it only has limited administrative authority, is not equipped with a monitoring system, and does not actively coordinate with the application provider. There is no official forum, summons, or coordination between the City Government and the application provider (Maxride). In fact, the application provider has stated its readiness to coordinate and contribute to supervision. The Makassar City Government does not yet have local regulations (Perda) governing the operation of online bajaj, so supervision is not carried out based on strong legal instruments. This reality shows a contradiction with the benefits. It is an indicator of a discrepancy with Siyasah Syar'iyyah. This study recommends the establishment of specific regional regulations, the formation of a regular coordination forum, and the integration of a technology-based monitoring system between the local government, the police, and the application provider.